Demand for environmental technological innovation in the manufacturing industry - Yusuf, Muhammad Fakhrul; Ashari, Hasbullah; Razalli, Mohd Rizal (Penerbit Universiti Malaysia Pahang, 2021)
Which is more environmentally friendly, paper bag or plastic bag? Choosing an alternative product or process that is more environmentally friendly is what it means for environmental technological innovation (ET-innovation). ET-innovation is the key concept that connects three pillars of economy, social and environment, in the world sustainable development agenda. Sustainable development is an international agenda accepted by all stakeholders, namely policy-makers, industry practitioners and the communities, to resolve current and future development problems. Hence, this book's original contribution to knowledge was the evaluation of the extent of market demand effects on ET-innovation implementation from the perspective of the demand-based view. This book also discussed market orientation as the mediator, and environmental turbulence and managerial ties as moderators. The investigation was done within the scope of the manufacturing industry in Malaysia. In conclusion, despite several limitations, this book has explained the demand for ET-innovation implementation in the Malaysian manufacturing industry. This book has also discussed market orientation to explain the issues, and deliberated the strength of the environmental turbulence and managerial ties in the linkages. Several practical situations have been derived to further assist readers to understand the book.